Splenic abscess, a rare complication in a case of sickle cell thalassemia - Ponathil, Ankitha; Rai, Rajesh; Inamdar, Prithi; Naulakha, Ravi (International Journal of Contemporary Pediatrics, 2024)
Sickle cell disease (SCD) is an inherited autosomal recessive haemoglobinopathy. Sickle cell beta thalassemia is a variant syndrome of SCD characterised by the compound heterozygosity for sickle and beta thalassemia genes. We present a case of 12 year old male child diagnosed case of sickle cell thalassemia at the age of 2 years with complaints of fever, yellowish discolouration of eyes and drowsiness. USG abdomen was done suggestive of splenomegaly, multiple ill-defined, heterogeneously hypo-echoic, areas scattered throughout the splenic parenchyma with no vascularity within likely representing as splenic micro-abscesses. Child was started on antibiotics covering anaerobic and gram-positive organisms (vancomycin, meropenem, amikacin and metronidazole). Currently child is doing well with huge relieve to his symptoms.